Evaluation of polypharmacy and potentially inappropriate medication use among geriatric individuals aged 80 years and older - Beler, Mehmet; Yakar, Burkay; Beler, Zeynep; Onalan, Erhan (Bmc, 2026)
Purpose The current study aimed to investigate the frequency of polypharmacy and potentially inappropriate medication use (PIMs) and associated factors among 80 years and older adults. Methods This cross-sectional and descriptive study was conducted among patients registered in the geriatrics clinic in Elazig city between February and May 2025. A total of 300 individuals aged 80 years and older were included in the study. The study involved outpatients and the interviews were performed at home. Sociodemographic and medical history of the participants were obtained through face-to-face interviews. Polypharmacy was defined as the regular use of five or more medications or prescription supplements simultaneously. Potential inappropriate drug use of the participants was evaluated with The AGS Beers Criteria 2023. Results The median number of medications used by the participants were 5.0 (0.0-12.0), the median number of current chronic diseases were 3.0 (0.0-8.0). The frequency of polypharmacy in the study population was 54.7% (n=164), and the frequency of PIM use was 78.0% (n=234). No statistically significant difference was found between the sociodemographic characteristics and polypharmacy. PIMs was more common in participants with incontinence (p =0.044). Statistically significant higher PIMs was found in participants with polypharmacy (p <0.001). Conclusion The current study showed that the prevalence of polypharmacy (54.7%) and PIM (78.0%) were very high in the older population. The increase in the number of chronic diseases and the number of medications used was associated with PIM. It is recommended that physicians providing services to the geriatric population should consider the risk of PIM and polypharmacy to reduce adverse drug effects.
Keywords: Potentially Inappropriate Medication; Polypharmacy; Older Adults